Assembly of α-synuclein and neurodegeneration in the central nervous system of heterozygous M83 mice following the peripheral administration of α-synuclein seeds - Jennifer A. Macdonald (BMC, 2021)
Abstract Peripheral administration (oral, intranasal, intraperitoneal, intravenous) of assembled A53T α-synuclein induced synucleinopathy in heterozygous mice transgenic for human mutant A53T α-synuclein (line M83). The same was the case when cerebellar extracts from a case of multiple system atrophy with type II α-synuclein filaments were administered intraperitoneally, intravenously or intramuscularly. We observed abundant immunoreactivity for pS129 α-synuclein in nerve cells and severe motor impairment, resulting in hindlimb paralysis and shortened lifespan. Filaments immunoreactive for pS129 α-synuclein were in evidence. A 70% loss of motor neurons was present five months after an intraperitoneal injection of assembled A53T α-synuclein or cerebellar extract with type II α-synuclein filaments from an individual with a neuropathologically confirmed diagnosis of multiple system atrophy. Microglial cells changed from a predominantly ramified to a dystrophic appearance. Taken together, these findings establish a close relationship between the formation of α-synuclein inclusions in nerve cells and neurodegeneration, accompanied by a shift in microglial cell morphology. Propagation of α-synuclein inclusions depended on the characteristics of both seeds and transgenically expressed protein.